2018
DOI: 10.1371/journal.pone.0197589
|View full text |Cite
|
Sign up to set email alerts
|

Using within-day hive weight changes to measure environmental effects on honey bee colonies

Abstract: Patterns in within-day hive weight data from two independent datasets in Arizona and California were modeled using piecewise regression, and analyzed with respect to honey bee colony behavior and landscape effects. The regression analysis yielded information on the start and finish of a colony’s daily activity cycle, hive weight change at night, hive weight loss due to departing foragers and weight gain due to returning foragers. Assumptions about the meaning of the timing and size of the morning weight change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 32 publications
1
35
0
2
Order By: Relevance
“…Much of the hive weight gain during these periods was probably due to nectar and pollen collection. Hive weight loss at night during a nectar and pollen flow has been attributed to moisture loss of the drying nectar and pollen 22 . Hives in almonds lost on average more than 12 g per h at night while hives in blueberries lost on average less than 7 g per h, which suggests that, assuming the water content of the collected nectar was similar between sites, there was more material to dry in the hives in almonds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the hive weight gain during these periods was probably due to nectar and pollen collection. Hive weight loss at night during a nectar and pollen flow has been attributed to moisture loss of the drying nectar and pollen 22 . Hives in almonds lost on average more than 12 g per h at night while hives in blueberries lost on average less than 7 g per h, which suggests that, assuming the water content of the collected nectar was similar between sites, there was more material to dry in the hives in almonds.…”
Section: Discussionmentioning
confidence: 99%
“…Weight data were detrended for each day by subtracting the hive weight estimate at midnight (or closest time thereafter) from each subsequent weight value over the next 24 h (see 22 ). The resulting within-day weight datasets were modeled using the "segmented" function in R (version 3.6.1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the daily amplitude of weight change has been used to infer bee colony size [4,5]. Recently, the within-day pattern of weight changes was analyzed using segmented linear regression [7]. It was concluded that the early morning weight loss was mostly due to foragers leaving.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics and spatial arrangement of these variables provide new quantitative data for sociometric analysis [36][37][38][39] and will be particularly interesting in the context of a collapsing colony. Colony-wide, high-resolution tracking augments larger-scale measures such as weight 55 and can be combined with additional hive sensors for a novel surveillance system 56 . The automatic nature of our approach also facilitates the imaging of multiple hives 57 , an important consideration due to colony-to-colony variability.…”
Section: Discussionmentioning
confidence: 99%